Are 'Village Doctors' in Bangladesh a curse or a blessing? - Wahed Tania; Hanifi S M A; Iqbal Mohammad; Mahmood Shehrin S; Bhuiya Abbas (BMC, 2010)
Abstract Background Bangladesh is one of the health workforce crisis countries in the world. In the face of an acute shortage of trained professionals, ensuring healthcare for a population of 150 million remains a major challenge for the nation. To understand the issues related to shortage of health workforce and healthcare provision, this paper investigates the role of various healthcare providers in provision of health services in Chakaria, a remote rural area in Bangladesh. Methods Data were collected through a survey carried out during February 2007 among 1,000 randomly selected households from 8 unions of Chakaria Upazila. Information on health-seeking behaviour was collected from 1 randomly chosen member of a household from those who fell sick during 14 days preceding the survey. Results Around 44% of the villagers suffered from an illness during 14 days preceding the survey and of them 47% sought treatment for their ailment. 65% patients consulted Village Doctors and for 67% patients Village Doctors were the first line of care. Consultation with MBBS doctors was low at 14%. Given the morbidity level observed during the survey it was calculated that 250 physicians would be needed in Chakaria if the patients were to be attended by a qualified physician. Conclusions With the current shortage of physicians and level of production in the country it was asserted that it is very unlikely for Bangladesh to have adequate number of physicians in the near future. Thus, making use of existing healthcare providers, such as Village Doctors, could be considered a realistic option in dealing with the prevailing crisis.